Pengaruh Keefektifan Pengendalian Internal, Ketaatan Aturan Akuntansi, dan Asimetri Informasi terhadap Kecenderungan Kecurangan Akuntansi - Rival Akbar; Fefri Indra Arza (Jurnal Eksplorasi Akuntansi, 2023)
This study aims to determine the effect of the effectiveness of internal control, compliance with accounting rules, and information asymmetry on the tendency of accounting fraud in Padang City Regional Apparatus Organizations. The sampling technique used was total sampling with a total of 104 respondents. The data were analyzed using multiple regression formulas with the help of the SPSS application. This study concludes that the effectiveness of internal control has no significant effect on the tendency of accounting fraud. Compliance with accounting rules has a significant positive effect on the tendency of accounting fraud. Information asymmetry has a significant positive effect on the tendency of accounting fraud.